ANALISIS FAKTOR YANG MEMPENGARUHI MINAT PENGGUNAAN FINTECH - Rafinda, Ascaryan; Bahy Raihan Rauf; Eliada Hewiyanti (Universitas Airlangga, 2024)
This research aims to identify and analyze the interest in the adoption of fintech and e -commerce applications among Micro, Small, and Medium Enterprises (UMKM) actors in Kebumen Regency, which is influenced by risk factors, self-confidence, subjective norms, perceived ease of use, and perceived usefulness. The methods used include multiple regression analysis, t-test, F-test, and coefficient of determination. The results of this study indicate that (1) risk does not have a significant negative influence on the interest in adopting fintech and e -commerce, (2) self-confidence has a significant favorable influence on the interest in adopting fintech and e -commerce, (3) subjective norms do not have a significant favorable influence on the interest in adopting fintech and e -commerce, (4) perceived ease of use does not have a significant favorable influence on the interest in adopting fintech and e - commerce, (5) perceived usefulness has a significant favorable influence on the interest in adopting fintech and e - commerce.